Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.20307/nps.2017.23.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins from Clitoria ternatea Attenuate Food-Borne Penicillium expansum and its Potential Application as Food Biopreservative

Abstract: − Clitoria ternatea or Commonly known blue pea, is a perennial climber crop native to Asian countries. The current study was aimed to evaluate the antimicrobial activity C. ternatea extract on food borne microorganisms and its antifungal effect on Penicillium expansum. The extract showed significant antimicrobial activity against 3 Gram positive bacteria, 2 Gram negative bacteria and 1 filamentous fungus on disc diffusion assay. The extract also showed good biocidal effect on all Gram positive bacteria tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
0
26
1
Order By: Relevance
“…(Havananda and Luengwilai, 2019). Blue pea flower is being eaten as vegetables in Southeast Asia (Leong et al, 2017) and blue pea flower extract has been used in desserts and beverages in Southeast Asian countries such as Malaysia and Thailand (Pasukamonset et al, 2017). Polyacylated derivatives of delphinidin 3,3 ,5 -triglucoside, named "ternatins" are the major anthocyanins present in blue pea flower (Terahara et al, 1990;Vidana Gamage et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…(Havananda and Luengwilai, 2019). Blue pea flower is being eaten as vegetables in Southeast Asia (Leong et al, 2017) and blue pea flower extract has been used in desserts and beverages in Southeast Asian countries such as Malaysia and Thailand (Pasukamonset et al, 2017). Polyacylated derivatives of delphinidin 3,3 ,5 -triglucoside, named "ternatins" are the major anthocyanins present in blue pea flower (Terahara et al, 1990;Vidana Gamage et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The results in table (2) showed that both extracts had the potential to inhibit the growth of three bacteria, except Escherichia coli and Salmonella typhi. Leong et al [24] also reported that Clitoria Ternatea L. extract did not show inhibition to Escherichia coli . However, an opposite result was found [2.14] .…”
Section: Determination Of Antimicrobial Activitymentioning
confidence: 97%
“…In terms of foodborne pathogenic bacteria, B. cereus, S. enterica illustrated higher inhibition zone among bacteria while E. coli and S. aureus demonstrated the lowest inhibition zone. The diameter of clear zones illustrated the different susceptibility of bacteria to the extracts (Leong et al, 2017). The antimicrobial effect for S. enterica and B. cereus were better than E. coli and S. aureus proving that freeze dried C. ternatea flowers were able to retard Gram-positive bacteria as well as Gram-negative bacteria.…”
Section: Encapsulation Efficiency (Anthocyanin Contents)mentioning
confidence: 98%